Correlation Between Physical Activity and Learning Concentration, Self-Management, and Interpersonal Skills Among Korean Adolescents - Jeonga Kwon; Su-Yeon Roh; Daekeun Kwon (Children)
This study aimed to investigate the association between physical activity participation and key developmental competencies—learning concentration, self-management, and interpersonal skills—among Korean adolescents. Data were drawn from the 2021 Study on the State of Play Culture of Children and Adolescents and Measures to Support Growth, conducted by the Korea Adolescent Policy Institute. The study participants included elementary, middle, and high school students in Korea, consisting of 1507 males (53.3%) and 1322 females (46.7%), totaling 2829. We analyzed the data using frequency distribution, chi-square test, and multivariate logistic regression. The results revealed a significant sex difference in the duration of physical activity, with boys spending more time engaging in physical activity than girls. In addition, time spent on physical activities decreased as the school grade level increased. Notably, the more time Korean adolescents spent engaging in daily physical activity, the higher they rated their learning concentration, self-management, and interpersonal skills. These findings suggest the need to promote greater physical activity among adolescents—particularly among girls—which can help improve learning concentration, self-management, and interpersonal skills.